Computational and conceptual understanding of the connections among standard deviations, z-scores, and normal distributions - Reyes, Melissa Lopez (Animo Repository, 2003)
A structure for learning the connections among standard deviations, z-scores, and normal distributions is presented. The components of this structure are classified into intuitive or previously learned conceptual knowledge, computational knowledge, and formalized conceptual knowledge. © 2003 Taylor & Francis Group, LLC.